The impact of spiritual and moral values of the youth on the Russian society civil culture - Tkacheva, N.A.; Belonozhko, L.N. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2017)
The authors conducted a sociological analysis of the spiritual and moral values of the youth and their impact on the civil culture, which largely determines the forms of individual and group social activity and the functioning of social institutions. The implementation of the key function of values, i.e. the achievement of material goods and the spiritual development, to a certain extent, will allow to overcome the cultural gap between elites and common citizens, which is considered one of the main reasons for the failure of reforms in Russia. The study of transformation processes determined great interest in the social potential of the youth as a subject of social reproduction, and the civil culture is a key factor and element of modernization for it changes and activates value orientations of the younger generations and leads to the qualitative transformations of all spheres of society. The article is based on the empirical data of a number of sociological surveys conducted in 2016 in five cities of the south of the Tyumen Region. The empirical data prove that there is an obvious emerging shift from paternalistic expectations, passivity and low estimates of the future to the rationality, individualization and self-reliance. The authors emphasize the influence of mass media as one of the factors of the civil culture formation, which is evident in the impact of media on the moral and spiritual values of the younger generations.